Role of free nitrous acid in wastewater treatment processes : action and inhibition - Ganda, Lily (2015)
In modern wastewater treatment plants (WWTPs), enhanced biological phosphorus removal (EBPR) is typically combined with nitrogen removal. Nitrite, an intermediate of nitrification and denitrification, can accumulate in the system under certain environmental conditions. However, free nitrous acid (FNA), a protonated form of nitrite, has been known to inhibit various microorganisms in WWTP, including poly-phosphate accumulating organisms (PAOs) and glycogen accumulating organisms (GAOs), the two functional groups of microorganisms competing in EBPR system. This study investigated the inhibitory effects of FNA on the key metabolisms of PAO and GAO as well as the inhibition reversibility. Different response of PAOs and GAOs to FNA was obtained, wherein GAOs were unable to utilize nitrite as electron acceptor as opposed to PAOs, suggesting that FNA can be used as a strategic tool to manipulate the microbial community structure in the EBPR system towards PAO enrichment, as also subsequently demonstrated in this thesis.